Supporting evidence for a human reservoir of invasive non-Typhoidal Salmonella from household samples in Burkina Faso. - Annelies S Post; Seydou Nakanabo Diallo; Issa Guiraud; Palpouguini Lompo; Marc Christian Tahita; Jessica Maltha; Sandra Van Puyvelde; Wesley Mattheus; Benedikt Ley; Kamala Thriemer; Eli Rouamba; Karim Derra; et al. (Public Library of Science (PLoS), 2019)
BACKGROUND:Salmonella Typhimurium and Enteritidis are major causes of bloodstream infection in children in sub-Saharan Africa. This study assessed evidence for their zoonotic versus human reservoir. METHODS:Index patients were children with blood culture confirmed Salmonella infection recruited during a microbiological surveillance study in Nanoro, rural Burkina between May 2013 and August 2014. After consent, their households were visited. Stool from household members and livestock (pooled samples per species) as well as drinking water were cultured for Salmonella. Isolates with identical serotype obtained from index patient and any household sample were defined as "paired isolates" and assessed for genetic relatedness by multilocus variable number tandem-repeat analysis (MLVA) and whole-genome sequencing (WGS). RESULTS:Twenty-nine households were visited for 32/42 (76.2%) eligible index patients: two households comprised two index patients each, and in a third household the index patient had a recurrent infection. Among the 32 index patients, serotypes were Salmonella Typhimurium (n = 26), Salmonella Enteritidis (n = 5) and Salmonella Freetown (n = 1). All Typhimurium isolates were sequence type (ST)313. Median delay between blood culture sampling and household visits was 13 days (range 6-26). Salmonella was obtained from 16/186 (8.6%) livestock samples (13 serotypes) and 18/290 (6.2%) household members (9 serotypes). None of the water samples yielded Salmonella. Paired Salmonella Typhimurium isolates were obtained from three households representing four index patients. MLVA types were identical in two pairs and similar in the third (consisting of two index patients and one household member). WGS showed a strong genetic relatedness with 0 to 2 core genome SNPs difference between pairs on a household level. Livestock samples did not yield any Salmonella Typhimurium or Salmonella Enteritidis, and the latter was exclusively obtained from blood culture. Other serotypes shared by human and/or livestock carriers in the same household were Salmonella Derby, Drac, Tennessee and Muenster. CONCLUSIONS/SIGNIFICANCE:The current study provides further evidence of a human reservoir for invasive non-Typhoidal Salmonella (iNTS) in sub-Saharan Africa.